Disintegration of the EU and the implications for ASEAN - Hooman Peimani (Asian Development Bank Institute (ADBI), 2020)
The EU has evolved from a grouping of six Western European countries with stated economic objectives to a large regional organization of now 27 European countries pursuing a wide range of political, economic, social, environmental, and security objectives, while the majority of the other European countries are associated with it or aspire to join it. The EU has been promoted as the main successful case of regional integration to be emulated by other regions. However, while its integration has been quite impressive, various developments have indicated the possibility of its disintegration. The threat of disintegration from within makes it even more worrisome as it reflects the growing discontent in some of its members with the way the EU is run under the leadership of its heavyweights (France and Germany), added to the EU's unfulfilled promises of growth, prosperity, and equality for all its members. Brexit ended a taboo and showed a way out of the EU for the dissatisfied EU members that will not likely be repeated in the foreseeable future. However, there are other possible scenarios for disintegration, including the degeneration of the EU into a loose regional grouping of convenience where its members take advantage of its benefits while pursuing their own national interests and following the EU's rules only when they serve their interests. ASEAN is much younger than the EU and has not sought, in practice, the same objectives pursued by the latter, although it has targeted regional integration in Southeast Asia. There is a degree of similarity in the circumstances under which the two regional groupings were established, but there are also various differences between the two regions. In a nutshell, ASEAN is a loose organization of 10 members who work together in certain areas of common interest, while mainly focused on their national objectives. Unlike the EU, it does not operate as a power bloc and contains a number of unresolved issues, which could pit its members against each other as they have done before. Consequently, if the EU, despite 70 years of planned integration with a significant degree of success, is not immune to disintegration, then ASEAN with its still insignificant degree of integration is surely vulnerable to such a possibility, unless it seriously initiates a process to address its root causes before it is too late.
Keywords: F52; F15; 330; regional integration; EU disintegration; European grouping; European Union; ASEAN integration; Southeast Asia and regional cooperation